THE RELATION BETWEEN OPERATIONAL EFFICIENCY AND TAX AGGRESSIVENESS IN BRAZIL - Paste Junior, Eloy; Martinez, Antonio Lopo (Revista Universo Contábil, 2020)
This paper studies whether there is a relation between the operational efficiency measured through the Data Envelopment Analysis (DEA) models and the tax aggressiveness of the Brazilian public companies listed on B3 between the period of 2010 to 2015. The main hypothesis is that companies that are more operational efficient are in average less tax aggressive. Or, in other words, we predict that the less operational efficient companies have usually to engage in tax aggressiveness strategies more often. An efficiency score was calculated considering the outputs and inputs of the companies, classifying them according to the Data Envelopment Analysis (DEA) models to determine the relative company’s operational efficiency. The tax aggressiveness was measured by the difference between the Effective Tax Rates (ETR) and the average of ETR of companies from specifics economic sectors. Five relevant economic sectors were evaluated. A Data Panel model was estimated using the fixed effects. Considering the regression of all sectors, the results confirmed the hypothesis that companies that are more operational efficient in average tend to be less tax aggressive. However, when the samples were separated by sectors, only in the Energy and Textile Sectors this relation is significant.